Analisis Penggunaan Frasa pada Teks Prosedur dalam Buku Bahasa Indonesia Bergerak Bersama Kelas V SD Kurikulum Merdeka (International Forum of Researchers and Lecturers, 2023)
This research was conducted to analyze the phrases in the procedural text in the Indonesian book Moving Together Class V SD Kurikulum Merdeka. This study focuses on analyzing phrases based on categories or word classes used in procedure texts. The purpose of this research analysis is to examine the use of adverb phrases, numerals, adjectives, nouns, and verbs in the Indonesian book Moving Together Class V SD Merdeka Curriculum. This study uses a methodological approach in the form of a qualitative descriptive approach and a theoretical approach in the form of a syntactic approach. The data in this study were taken from fragments of phrases in procedural texts in the Indonesian book Moving Together Class V SD Kurikulum Merdeka. The results of this study are that there are 9 noun phrases or nouns, 8 adverb phrases or adverbs, 2 verb or verb phrases, 2 adjective phrases or adjectives, and 1 numeral phrase or number word. The benefit of this research is to find out the types of phrases in the procedural text in the book Indonesian Moving Together for class V at the Merdeka Curriculum Elementary School as well as provide initial knowledge about phrases to fifth-grade elementary school students as an introductory knowledge to continue to the next level of education.